PENGARUH LITERASI KEUANGAN DAN LITERASI DIGITAL TERHADAP PERTUMBUHAN UMKM DI KECAMATAN RAPPOCINI KOTA MAKASSAR - Nurjannah Nurjannah; Hikmayani Subur (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
This study aims to analyze the influence of financial literacy and digital literacy on the growth of Micro, Small, and Medium Enterprises (MSMEs), specifically in the culinary sector in Rappocini District, Makassar City. The research method used is a quantitative approach with data collection techniques through surveys and questionnaires distributed to MSME actors in the Rappocini District, Makassar City. The research sample consists of 102 informants, calculated as 25% of the total population of 408 MSMEs in the area. The results of the study indicate that financial literacy and digital literacy have a significant impact on the growth of MSMEs. Financial literacy helps MSME owners manage their finances better, while digital literacy enables them to utilize technology for more efficient marketing and operations. The conclusion of this study is that increasing financial and digital literacy can substantially promote the growth of MSMEs. Therefore, it is recommended to have training and education programs focusing on these two aspects to support the sustainability and expansion of MSMEs in the Rappocini District.